Letter Wardang Farm, Sturt [S. Aust.] to Mrs Ableton, London - Wilson, Alfred; Ableton, Mrs. (1844)
Letter describes conditions of contemporary life in South Australia - the harvest and Ridley's new "reaping machines", Sturt's setting out from Adelaide to explore the interior, etc.
Manuscript reference no. : NLA MS 2748.
Photocopy.
Original held by Argyll Stamp Company, London W.C.2.
Keywords: Wilson, Alfred -- Correspondence; Ridley, John, -- 1806-1887.; Ableton, -- Mrs. -- Correspondence; Sturt, Charles, -- 1795-1869.; Pioneers -- South Australia -- Correspondence; Harvesting machinery -- South Australia; South Australia -- Social life and customs -- 1836-1851.; South Australia -- Discovery and exploration; Pioneers